Rancang Bangun Alat Pendeteksi NOx dan CO Berbasis Mikrokontroler ESP32 dengan Notifikasi Via Telegram dan Suara - Asmazori, Mutiara (Universitas Andalas, 2021)
The design of NOx and CO detectors based on notifications via telegram and voice has been carried out. This detector consists of a gas sensor MQ-135 as a nitrogen oxide detector and an MQ-7 sensor as a carbon monoxide detector. Data processing is carried out using an ESP32 microcontroller which can send results to a telegram bot and play sound using speakers connected to the ISD 1820 sound module. The tool made can send notifications if the concentration of nitrogen oxides and carbon monoxide exceeds 50 ppm. The test is carried out by burning waste to produce smoke. Burning smoke contains various gases and particles that are harmful to the body. The characterization of the MQ-135 sensor was carried out by comparing the data obtained from the ISPU to measure nitrogen oxide gas and producing an error value of 9.09%. Meanwhile, the characterization of the MQ-7 sensor was carried out using a biogas analyzer and resulted in an error ratio of 3.26%. These results prove that the tools that have been designed can work well.